Learning agenda: Climate-smart agriculture and gender - Puskur, Ranjitha; Mishra, Avni (CGIAR GENDER Impact Platform, 2024)
The CGIAR GENDER Impact Platform has developed a learning agenda focused on the intersection of climate-smart agriculture (CSA) and gender equality. The purpose of the learning agenda is to inform a short- to medium-term research strategy on how gender equality in agrifood systems can be advanced through CSA.